QUALITY OF LIFE OF THE POPULATION AS A SCIENTIFIC CATEGORY: THEORETICAL APPROACHES TO DEFINITION (European Journal of Economics, Finance and Business Development, 2026)
In contemporary scientific circles, intense discussions persist regarding the definition of the concept of the "quality of life of the population." To date, a definitive academic consensus has not yet been reached. The primary conceptual challenge lies in delineating the precise boundaries and theoretical differences between two interconnected categories: the "standard of living" and the "quality of life."